Saturation mutagenesis identifies activating and resistance-inducing FGFR kinase domain mutations - Tangermann, Carla; Ghosh, Avantika; Ziegler, Martin; Facchinetti, Francesco; Stappenbeck, Jannis; Carus Sahin, Yagmur Oyku; Riester, Marisa; Viardot, Luise Carmina; Zundel, Tobias; Friboulet, Luc; Hollebecque, Antoine; Naveja, José J.; et al. (Nature genetics, 2025)
Variants of uncertain significance represent the biggest challenge for genomics-based precision oncology. Activated fibroblast growth factor receptors (FGFRs) frequently drive tumorigenesis by different genetic aberrations. However, it remains unknown which of the many point mutations affecting FGFR1, FGFR2, FGFR3 or FGFR4 in cancer are druggable, that is, activating signaling while not mediating FGFR inhibitor resistance. Here we implemented a saturation mutational scanning platform to screen all 11,520 possible point mutations covering the kinase domains of FGFR1-4. Pooled positive selection screens identified 474 activating and 738 mutations mediating resistance to the FGFR inhibitors pemigatinib and futibatinib, together revealing 301 druggable FGFR mutations analogous to a strong PS3/BS3 evidence level. The screens also identified loss-of-function mutations and an association of gain-of-function mutations with hydrophobic changes. The functional screens identified 97% of acquired resistance mutations in clinical trials. Our comprehensive catalog of every druggable mutation in the FGFR kinase domains is readily available for clinical decision support.
Gesehen am 13.01.2026